HUBUNGAN KOORDINASI MATA-TANGAN, POWER TUNGKAI DAN PERCAYA DIRI TERHADAP HASIL KETERAMPILAN LAY-UP SHOOT - Meirijal, Yopi (Jurnal Olahraga, 2015)
The objectives to be achieved in this study are to find out: (1) The direct relationship of eye-hand coordination to the results of lay-up shoot skills in basketball games. (2) The direct relationship of leg power to the results of lay-up shoot skills in basketball games. (3) Direct relationship of confidence in the results of lay-up shoot skills in basketball games (4) A joint relationship between Eye-Hand Coordination, power and confidence in lay-up shooting skills in basketball games. The research method used to achieve research results using descriptive with correlational studies. The population was taken from the 2012-2013 class of students at the Pasundan Cimahi STKIP campus, the population taken was 133 people while the sample was 80 people. Based on the results of research and the results of data analysis that has been carried out, the following data can be obtained: (1) There is a significant relationship between eye coordination with lay-up shoot skills in basketball. (2) There is a significant relationship between leg power and lay-up shoot skills in basketball. (3) There is a significant relationship between self-confidence and lay-up shoot skills in basketball. (4) There is a significant joint relationship between eye-hand coordination, leg power and confidence in the results of shoot lay-up skills in basketball